Successful Myomectomy during Pregnancy for a Large Uterine Fibroid Causing Intestinal Obstruction: Report of a Case - Mainul, Haque; Naghem Farouk, Abed; Wisam Abdul Kadder, Yassin (EManuscript Services, 2015)
Myomectomy is a rare decision taken by O & G specialist in the management of uterine fibroids during pregnancy because hazardous outcome. Management of uterine fibroids during pregnancy is usually expectant making myomectomy a rather rare possibility. This is why surgical removal is generally delayed until after delivery. The current case was a large, symptomatic multiple uterine myomas causing pressure symptoms and was diagnosed during pregnancy by ultrasound and successfully managed by antepartum myomectomy retaining the fetus alive in utero at 18-20 weeks gestation. At term, the patient was delivered by Caesarian hysterectomy due to the presence of multiple myomas occupying the lower segment with placenta accrete, and uncontrolled blood loss from the placental bed. The patient remained uneventful in next 20 weeks follow-up. This case demonstrates the safety of myomectomy during pregnancy in special circumstances such as intestinal obstruction caused by external compression by a big fibroid.